1998
DOI: 10.1074/jbc.273.8.4293
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Methylesterase Regulates Methanol and Ethanol Accumulation in Ripening Tomato (Lycopersicon esculentum) Fruit

Abstract: We provide genetic evidence that the production of methanol in tomato fruit is regulated by pectin methylesterase (PME, EC 3.1.1.11), an enzyme that catalyzes demethoxylation of pectins. The role of PME in methanol production in tomato fruit was examined by relating the tissue methanol content to the PME enzymatic activity in wild-type Rutgers and isogenic PME antisense fruits with lowered PME activity. In the wild-type, fruit development and ripening were accompanied by an increase in the abundance of PME pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 15 publications
7
83
0
Order By: Relevance
“…Concerning the metabolism related methanol release, Frenkel et al (1998) found that methanol within the leaf is mostly produced as a consequence of the demethylation of the pectin matrix, a necessary step in the extension of the cell walls during plant growth. On the basis of the pectin content, Galbally and Kirstine (2002) distinguished between two major cell wall types with a high or low potential for methanol release.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the metabolism related methanol release, Frenkel et al (1998) found that methanol within the leaf is mostly produced as a consequence of the demethylation of the pectin matrix, a necessary step in the extension of the cell walls during plant growth. On the basis of the pectin content, Galbally and Kirstine (2002) distinguished between two major cell wall types with a high or low potential for methanol release.…”
Section: Introductionmentioning
confidence: 99%
“…In higher plants, it is known to be a cell wall associated protein and several of the PME cDNA available in the literature, are known to have toward the N-terminal sequence, a characteristic signal peptide which is thought to help in targeting the protein to the plant cell wall (Gaffe et al 1997 and references therein). PME catalyzes the deesterification of galactosyluronate methylesters of pectins, releasing protons and methanol into the media (Frenkel et al 1998). Despite the biochemical mode of action of PME is well known, it have been difficult to demonstrate any role for PME in the physiology of plants.…”
Section: *Corresponding Authormentioning
confidence: 99%
“…Several studies have shown a strong correlation between PME activity or PME gene expression and physiological processes such as hypocotyls elongation (Bordenave and Goldberg, 1994;Derbyshire et al, 2007)), fruit ripening and maturation (Tieman and Handa, 1994;Prasanna et al, 2007), cellular adhesion (Roberts et al, 2000), seed germination (Ren and Kermode, 2000), cambial cell differentiation (Micheli et al, 2000) and cell growth in developing wood cells (Siedlecka et al, 2008). Other studies have shown that PME acts as methanol source (Frenkel et al, 1998) and also as host-cell receptor for Tobacco Mosaic Virus (TMV) (Dorokhov et al, 1999;Chen et al, 2000). Recent studies demonstrated the role of PMEs in disease resistance and abiotic stress tolerance .…”
Section: Research Articlementioning
confidence: 99%